Implantable Cardioverter‐Defibrillators and Cardiac Resynchronization Therapy in Older Adults With Heart Failure. Issue 10 (12th August 2019) - Sandhu, Amneet; Levy, Andrew; Varosy, Paul D.; Matlock, Daniel
Abstract : BACKGROUND/OBJECTIVES: Implantable cardioverter‐defibrillators (ICDs) and cardiac resynchronization therapy (CRT) are cardiac implantable electronic devices that may improve morbidity and mortality in select patients with heart failure. Although the benefits of these devices have been well defined, competing mortality risks, comorbid conditions, and frailty pose difficulty in determining risk‐benefit trade‐offs when these options are considered for older adults. CONCLUSION: In this review, we focus on the benefit, risk, and use of ICD and CRT in older adults, particularly because the goals of care for many older adults include a shift away from life‐prolonging interventions. Additionally, we discuss periprocedural risk, cost, and maintenance in older populations. Finally, we introduce a framework for helping clinicians and older adults make these challenging decisions collectively. J Am Geriatr Soc 67:2193–2199, 2019